Métabolisme territorial et filières de récupération-recyclage : le cas des déchets d’équipements électriques et électroniques (DEEE) en Midi-Pyrénées. - Jean-Baptiste Bahers (Développement Durable et Territoires)
This work focuses on the treatment of Waste Electrical and Electronic Equipment (WEE). It reveals how the local recycling system contributes to the development of territorial ecology. This work shows how WEEE’s management interacts with European and French legislative frameworks. Based on a material flow analysis of the recovery-recycling chain, this study shows the strategic issues of the chain’s metabolism which results from the dynamics of the various organizations involved. Territorial metabolism reveals the difference between objectives of environmental pollution control and the increase of material flows.